PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Iin Sunarti; Dwi Nita Nurul Fadilah (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2019)
Abstract: The purpose of this study was to find out: differences in the final test (posttest) in the experimental class using the Problem Based Learning learning model and the control class using conventional models, and to determine the increase (Gain) of critical thinking skills of students in the experimental class using learning models Problem Based Learning and control classes that use conventional models. The method used in this study was Quasi Experiment. Quasi experiments, which are quasi-experimental methods, cannot control all variables that affect the course of research. The results showed that there were differences in the final test (posttest) in the experimental class with the control class. Then it can be concluded accept the research hypothesis (Ha) and reject the null hypothesis (Ho). There is an increase (gain) the critical thinking ability of the experimental class students who use the Problem Based Learning learning model with the control class that uses conventional models (lectures). In other words “Problem Based Learning learning models can improve students’ critical thinking skills compared to conventional learning models (lectures)”. Based on the results of the study it can be concluded that students' critical thinking skills are sufficient, but on this occasion the authors will provide suggestions as follows: need to allocate sufficient time because the application of the PBL learning model requires a considerable amount of time, in group division must divide equally between students who are active with students who are passive.Kata kunci : Kemampuan Berpikir Kritis Siswa, Problem Based Learning (PBL).